Animal magic using the health and social care standards for looked after children - Mary Morris (Scottish Journal of Residential Child Care)
The article advocates taking a positive, proactive approach to having animals and pets in the lives of looked after children. Links are made with the new Health and Social Care Standards. The life enhancing difference that animals can make for some looked after children in promoting their self-esteem and resilience are explored.